Reflexões sobre autoria e apropriação na arte contemporânea : de Adrian Piper a Zoe Leonard - Bernardina, Flávia Sangiorgi Dalla (2020)
This is a master's dissertation in Visual Arts whose purpose is to debate authorship and appropriation in contemporary art, with a focus on the production of two North American artists: Adrian Piper and Zoe Leonard. In order to analyze their artistic practices, we begin the journey analyzing appropriation in modern art from the relations of representation and power, and then moving forward in the study of appropriation in allegorical and in site-specific procedures in contemporary times, without losing sight of institutional criticism and identity issues that are intertwined in the artistic processes analyzed. At the same time, we analyze the path of authorship in contemporary times, taking as a guideline the notions brought by Marcel Duchamp in the “creative act”, in “the death of the author”, by Roland Barthes and in the “author as a function”, by Michel Foucault and the voice of the women, from Nelly Richard’s feminist writings and Dijamila Ribeiro’s place of speech of black feminism. When entering the research cut, we started to analyze some works of the artists Adrian Piper and Zoe Leonard, who update questions of appropriation and authorship in their artistic practices and debate relevant issues when making contemporary art